Proof: Changing the Log Base

Let's prove the following theorem:

logbx = (logkx) / (logkb)

Proof:

View as a tree | View dependent proofs | Try proving it

Additional Assumptions
1 logkx = i
2 logkb = j
3 logbx = k
4 not (j = 0)
Proof Table
# Claim Reason
1 ki = x if logkx = i, then ki = x
2 kj = b if logkb = j, then kj = b
3 bk = x if logbx = k, then bk = x
4 bk = ki if bk = x and ki = x, then bk = ki
5 (kj)k = bk if kj = b, then (kj)k = bk
6 (kj)k = k(jk) (kj)k = k(jk)
7 ki = k(jk) if (kj)k = bk and bk = ki and (kj)k = k(jk), then ki = k(jk)
8 i = jk if ki = k(jk), then i = jk
9 k = i / j if i = jk and not (j = 0), then k = i / j
10 logbx = (logkx) / (logkb) if logkx = i and logkb = j and logbx = k and k = i / j, then logbx = (logkx) / (logkb)

Comments

Please log in to add comments